The concept of khiar rukyat according to Imam Abu Hanifah: An analysis of the concept, legal evidence, and implementation - Hidayat, Enang (IAIN Syekh Nurjati Cirebon, 2024)
The validity of khiar rukyat (inspection option) according to Imam Abu Hanifah is considered absolute. However, the khiar rukyat he proposed is similar to bai al-gharar. The purpose of this research is to understand khiar rukyat according to Imam Abu Hanifah, the legal evidence, and its implementation in contemporary commercial contracts. This research falls under the category of normative Islamic legal research within the realm of doctrine (thought) using a conceptual approach. The data collection technique involves document analysis. The analysis utilizes prescriptive analysis of primary sources from the Hanafi school of thought, such as